Зайкин урожай: [для детей дошкольного возраста / И. В. Гурина ; художник О. И. Сунцова] - Гурина Ирина Валерьевна (Первое чтение, 2018)
Экземпляры: (20220609) / Инвентарный номер: 5720 / Цена: / Сис.шифр: Д / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6